Geopolymer double fluid grouting material for road base reinforcement and preparation method thereof - YU HONGBO; CHEN YANQIN; LI PENGHUI; WU CHAOFAN; LI HUI'AN (2017)
The invention discloses a geopolymer double fluid grouting material for road base reinforcement. The material is formed by mixing a component A and a component B in a weight ratio of 3: 1. The component A is composed of the following materials in parts by weight: 60-70 parts of blast furnace slag micro-powder, 6-8 parts of an alkaline excitant, 1-3 parts of a stabilizer and 10-30 parts of water; the component B is composed of the following materials in parts by weight: 7-20 parts of polypropylene glycol, 9-15 parts of water, 60-80 parts of water glass, 2-6 parts of sorbitol, 0.5-2.5 parts of a surfactant and 1-3 parts of a catalyst. The invention further discloses a preparation method of the geopolymer double fluid grouting material for road base reinforcement. The double fluid grouting material prepared by the preparation method is excellent in performance and low in cost. 本发明公开了种用于道路基层加固的地聚合物双液注浆材料，由A组分和B组分按3：1的重量比混合而成；所述A组分由以下材料按照重量份组成：高炉矿渣微粉60～70份、碱性激发剂6～8份，稳定剂1～3份，水10～30份；所述B组分由以下材料按照重量份组成：聚丙二醇7～20份、水9～1